2019
DOI: 10.2298/pac1904349q
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the dielectric and multiferroic properties of Co0.5Zn0.5Fe2O4/Ba0.8Sr0.2TiO3 composite ceramics

Abstract: Co 0.5 Zn 0.5 Fe 2 O 4 /Ba 0.8 Sr 0.2 TiO 3 (CZFO/BST) composite ceramics with different molar ratios (1:3, 1:2, 1:1, 2:1 and 3:1) were prepared by combining chemical co-precipitation and sol-gel method. Effects of molar ratio on the microstructure, dielectric and multiferroic properties were investigated. The formation of the individual phases and the composites was confirmed by XRD results and small amount of secondary phase (Ba 2 Fe 2 Ti 4 O 13 ) was observed. The grain sizes of magnetic (CZFO) and ferroele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The P-E curve of the ceramics was selected at high frequency to reduce the effect of leakage current on the ferroelectric hysteresis loop. However, because of the presence of impurities, pores and grain boundaries, the leakage current cannot be ignored and will have a great influence on these measurement results, such as P r and E c will be overestimated [14]. The behaviour of ferroelectric hysteresis loop was consistent with that of the previously discussed sample leakage current.…”
Section: Dielectric Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…The P-E curve of the ceramics was selected at high frequency to reduce the effect of leakage current on the ferroelectric hysteresis loop. However, because of the presence of impurities, pores and grain boundaries, the leakage current cannot be ignored and will have a great influence on these measurement results, such as P r and E c will be overestimated [14]. The behaviour of ferroelectric hysteresis loop was consistent with that of the previously discussed sample leakage current.…”
Section: Dielectric Propertiessupporting
confidence: 83%
“…Composite multiferroic materials take advantage of the ME coupling between two or more single-phase compounds without multiferroic properties, thus, the composite material with a good ME coupling effect is Z. Zeng et al / Processing and Application of Ceramics 14 [3] (2020) 223-230 formed. It was found that the ME coupling coefficient of composite materials was several times higher than that of single-phase materials [14][15][16]. Composite multiferroic materials are generally composed of ferroelectric and ferromagnetic phase materials.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the value is close to zero with the Debye relaxation model; therefore, it can be inferred that the mechanism of xCCFO-y(BTO-BA) composite ceramics is the Maxwell-Wagner model from Figure 5b,d,f,h, which has been investigated by other groups as well. [20,[22][23][24][25][26][27][28] The dielectric constant of the specimens decreases first and then increases with the increase of y. This nonlinear change can be elucidated by the function phase (ferromagnetic or ferroelectric phase).…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…However, due to the different sintering temperatures of the constituent phases, it is easy to cause various problems such as cofiring mismatch 17 for different compositions, insufficient bonding of ceramic grains, and hindered stress-strain transfer, 18 which is not conducive to the performance of the sample. 19 To solve these problems, some researchers have optimized the properties of composites by adjusting the composition, 20 changing the preparation process, 21 designing different structures, 22 adding combustion aids, 23 etc.On the basis of previous studies, it is known that adding combustion aids can address the mismatch phenomenon during ceramic cofiring, reduce the sintering temperature, and increase the density. [24][25][26] Although it is possible to adjust the properties of composite ceramics by adding sintering aids, the grain size, density, etc.…”
Section: Introductionmentioning
confidence: 99%